On-chip integrated graphene aptasensor with portable readout for fast and label-free COVID-19 detection in virus transport medium. Issue 4 (1st July 2022) - Xu, Lizhou; Ramadan, Sami; Rosa, Bruno Gil; Zhang, Yuanzhou; Yin, Tianyi; Torres, Elias; Shaforost, Olena; Panagiotopoulos, Apostolos; Li, Bing; Kerherve, Gwilherm; Kim, Dong Kuk; Mattevi, Cecilia; et al.
Abstract : On-chip integrated graphene field-effect transistor (GFET)-based aptasensor was developed with portable readouts for sensitive and specific virus detection. Abstract : Graphene field-effect transistor (GFET) biosensors exhibit high sensitivity due to a large surface-to-volume ratio and the high sensitivity of the Fermi level to the presence of charged biomolecules near the surface. For most reported GFET biosensors, bulky external reference electrodes are used which prevent their full-scale chip integration and contribute to higher costs per test. In this study, GFET arrays with on-chip integrated liquid electrodes were employed for COVID-19 detection and functionalized with either antibody or aptamer to selectively bind the spike proteins of SARS-CoV-2. In the case of the aptamer-functionalized GFET (aptasensor, Apt-GFET), the limit-of-detection (LOD) achieved was about 10 3 particles per mL for virus-like particles (VLPs) in clinical transport medium, outperforming the Ab-GFET biosensor counterpart. In addition, the aptasensor achieved a LOD of 160 aM for COVID-19 neutralizing antibodies in serum. The sensors were found to be highly selective, fast (sample-to-result within minutes), and stable (low device-to-device signal variation; relative standard deviations below 0.5%). A home-built portable readout electronic unit was employed for simultaneous real-time measurements of 12 GFETs per chip. Our successful demonstration of a portable GFET biosensing platform has high potential for infectious disease detection and other health-care applications.